2019
DOI: 10.7717/peerj.8107
|View full text |Cite
|
Sign up to set email alerts
|

A new insight to biomarkers related to resistance in survived-white spot syndrome virus challenged giant tiger shrimp,Penaeus monodon

Abstract: The emergence of diseases such as white spot disease has become a threat to Penaeus monodon cultivation. Although there have been a few studies utilizing RNA-Seq, the cellular processes of host-virus interaction in this species remain mostly anonymous. In the present study, P. monodon was challenged with WSSV by intramuscular injection and survived for 12 days. The effect of the host gene expression by WSSV infection in the haemocytes, hepatopancreas and muscle of P. monodon was studied using Illumina HiSeq 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…Cactus is phosphorylated, dislocated from Dorsal, and degraded, while NF-κB transcription factor Dorsal translocated into the nucleus to activate the expression of AMPs 28 , 78 . In P. monodon , Toll-like receptors (TLRs) have been reported as part of shrimp defense mechanisms against pathogen invasion 79 , 80 . Expression of TLR transcripts of P. monodon larva and adult are inducible upon exposure to V. harveyi 80 , 81 , suggesting their involvement in activating shrimp immune responses against pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Cactus is phosphorylated, dislocated from Dorsal, and degraded, while NF-κB transcription factor Dorsal translocated into the nucleus to activate the expression of AMPs 28 , 78 . In P. monodon , Toll-like receptors (TLRs) have been reported as part of shrimp defense mechanisms against pathogen invasion 79 , 80 . Expression of TLR transcripts of P. monodon larva and adult are inducible upon exposure to V. harveyi 80 , 81 , suggesting their involvement in activating shrimp immune responses against pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of high-throughput RNA sequencing technologies, including RNA sequencing (RNA-seq), more and more studies use RNA-seq to expose the immune molecular mechanism of shrimp against viral infections, bacterial infections, and environmental stress (Kurita and Nakajima, 2012;Wang et al, 2014;Zeng et al, 2014;Qin et al, 2018;Jin and Zhu, 2019;Nian et al, 2019;Duan et al, 2020). Among them, hemocytes were widely used in transcriptome studies of shrimp virus infections, such as WSSV, TSV, and DIV1 (Sookruksawong et al, 2013;Ghani and Bhassu, 2019;Wang et al, 2019;. Therefore, the immune molecular mechanism of shrimp against a virus infection can be better understood by using the transcriptome analysis of hemocytes combined with enzyme activity study.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome analysis, which can be used to improve understanding of the genes underlying host response to disease, can also facilitate the identification of biomarkers for specific diseases as reported in compelling studies (Stockhammer et al, 2010;Zhu et al, 2017;Klett et al, 2018). A prior study identified three genes as new potential candidates for white spot syndrome virus resistance markers in giant tiger shrimp using transcriptome analysis (Mohd Ghani and Bhassu, 2019). One previous study identified a total of 24 key genes involved in multiple KEGG signaling pathways in Japanese flounder infected with Edwardsiella by sequencing the gill transcriptome and analyzing the gene interaction network .…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers contributing to the genetic resistance of the yellow catfish to bacterial infections were also established using transcriptome analysis . Similarly, prior studied used RNA-seq to uncover the transcriptome changes of Penaeus monodon that suffered from white spot syndrome virus and acute hepatopancreatic necrosis disease (Mohd Ghani and Bhassu, 2019;Soo et al, 2019). However, the research data cited above were generated by the second-generation sequencing technology, which meant that short-read sequence prevented the assembly of long transcripts (Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%